Performance Management Systems – Proposing and Testing a Conceptual Model - Șerban Radu-Alexandru; Herciu Mihaela (Studies in Business and Economics, 2019)
The utility of performance measurement and management system can be said to have been proven, but the problem faced by both the theoreticians and practitioners is to set the right performance indicators. Developed models are tools that managers can use to measure and manage performance, but they need to be tailored to the context. Also, the trend towards using non-financial performance indicators makes it very difficult for managers to design a performance measurement and management system because it involves the integration of qualitative and non-quantitative variables and a profound understanding of the internal and external environment of the company.